Science as an Art of Detachment - Santaella, Lucia (Circumscribere International Journal for the History of Science, 2009)
One of the concerns of Charles S. Peirce was the status of science, neither as a corpus of stagnant knowledge nor as a method of acquiring knowledge, but as a living body, animated by a particular spirit and a practice by living human beings. As a lifestyle of living scientists, according to Peirce, science is the inquiry of truth for its own sake. It is not knowledge but a life devoted to the quest for knowledge. As a consequence, he made a strict demarcation between scientific research and practical or technological action. On the other hand, Peirce was also aware of the limits of science and the illegitimacy of pretensions to judge faith and morality by scientific methods, as the latter require degrees of certainty more proper to belief than to science. Science and religion, although sharing in some points, have their own singular spirit. Whereas the latter is conservative and risks becoming fundamentalism when one’s beliefs are imposed unto others, the former is characterized by humbleness, open to the potentials of uncertainty, indetermination, chance and innovation.